Scale Up Strategy of Smoked Fish Home Industry Using AHP and SAST: A Case Study in Kendal District, Central Java Indonesia - Nugroho Sukamdani; Kholil Kholil (Muhammadiyah University Press, 2021)
Smoked fish is one of the most potential home industry in Kendal Regency in Central Java Province. It has a big impact to family economic development for poor people, and able to absorb a very large workforce. Although its role is very significant, the government's attention is still very limited, and most of their lives are still not prosperous. The purpose of this research is to develop a business scale up strategy in accordance with objective of home industry entrepreneurs condition using the SAST and AHP method. The results of the study showed that government’s support and policy through guarantee of raw materials is the most important factors for ensuring sustainability of smoked fish home industry, while to increase their business scale product diversification is the most appropriate strategy. There are two actors who have a big role in the development of smoked fish home industry in Kendal Regency, Regional Planning and Development Agency and Regional People Representative Council.